On the applicability of 2D URANS and SST k-ω turbulence model to the fluid-structure interaction of rectangular cylinders - Nieto, F.; Hargreaves, David; Owen, John S.; Hernández, S. (Taylor & Francis, 2015)
In this work the practical applicability of a 2D URANS approach adopting a block structured mesh and Menter's SST k-ω turbulence model in fluid-structure interaction (FSI) problems is studied using as a test case a ratio B/H = 4 rectangular cylinder. The vortex-induced vibration (VIV) and torsional flutter phenomena are analyzed based on the computation of the out-of-phase and in-phase components of the forced frequency component of lift and moment coefficients when the section is forced to periodically oscillate both in heave and pitch degrees of freedom. Also the flutter derivatives are evaluated numerically from the same forced oscillation simulations. A good general agreement has been found with both experimental and numerical data reported in the literature. This highlights the benefits of this relatively simple and straightforward approach. These methods, once their feasibility has been checked, are ready to use in parametric design of bridge deck sections and, at a later stage, in the shape optimization of deck girders considering aeroelastic constraints.